Mobility during the early islamic period: a means of power preservation for the ruling elite - Bloch, Franziska (Zeitschrift für Orient-Archäologie, 2013)
When discussing the rural residences of the Umayyads, the so called desert castles, it has repeatedly been argued for a temporary use of these establishments and thus for some sort of mobile court. Using the example of Jabal Says in Syria an attempt is being made to provide concrete evidence for such a limited pattern of use.